KAJIAN BIOMASSA POHON PADA LONGSOR AKTIF DI BAGIAN HILIR DAS BOMPON MAGELANG JAWA TENGAH - Gilang Samudra; Rido Koja; Azhari Syarief (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
Biomass is the total amount of living material on the surface of a tree and expressed in units of tons of dry weight per unit area (Brown (1997) in Sutaryo (2009)). The area in the Bompon watershed has a high vegetation density which has a role as a source of daily, monthly, seasonal and annual income for the community. The purpose of this study was to determine the total aboveground biomass in a tree and its effect on avalanches in the Bompon watershed. The method used in this study is the calculation of biomass is a non-harvest sampling method. The calculated biomass of trees is biomass on the surface covering parts of the tree such as: branch branches, and leaves. The allometric approach uses the biomass equation that has been developed before, so that in this activity only the diameter (dbh) and tree height results of the inventory (Land Range Research Group, 2016) are needed. The results showed that in the downstream part of the Bompon watershed it was categorized as an active landslide with a type of landslide namely slide. The location consists of two parts, namely the top of the hill and the middle slope with the use of mixed garden land. The recapitulation conducted shows that there are 143 trees. Calculation of the biomass analyzed at the top of the hill and the middle slope was 231.8488 kg at the top of the hill and 995.9895 kg at the middle slope.